Writing the research paper: A handbook with both the MLA and APA documentation styles - Anthony C Winkler (Harcourt Brace College, 1994)
The book provides specific information on the conventions of the research paper in a readily accessible handbook format. It explains research conventions as briefly as possible. The book partitions its expanations into digestible topics that can be read separately without any loss of continuity